2016
DOI: 10.1007/s10646-016-1681-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal and predator stressors in larval southern toads (Anaxyrus terrestris)

Abstract: Natural and anthropogenic stressors typically do not occur in isolation; therefore, understanding ecological risk of contaminant exposure should account for potential interactions of multiple stressors. Realistically, common contaminants can also occur chronically in the environment. Because parental exposure to stressors may cause transgenerational effects on offspring, affecting their ability to cope with the same or novel environmental stressors, the exposure histories of generations preceding that being te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
1
15
1
Order By: Relevance
“…Similar to our data, the latter study also found a precipitous decrease in juvenile survival, with only 17% surviving after the first month (Earl and Semlitsch 2013). Our study indicates carryover and latent effects of parental source and larval metal exposure on juvenile survivorship, because there were no treatment effects on survival to metamorphosis (Rumrill et al 2016), but such effects did manifest in terrestrial-stage juveniles, with survival reduced to 19.9 AE 4.5% in the toads that were exposed to elevated Cu and were from D-Area parents. Our time-to-death analysis also suggests that either parental or larval metal contaminant exposure can result in deleterious effects, which are increased with the combination of the 2.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to our data, the latter study also found a precipitous decrease in juvenile survival, with only 17% surviving after the first month (Earl and Semlitsch 2013). Our study indicates carryover and latent effects of parental source and larval metal exposure on juvenile survivorship, because there were no treatment effects on survival to metamorphosis (Rumrill et al 2016), but such effects did manifest in terrestrial-stage juveniles, with survival reduced to 19.9 AE 4.5% in the toads that were exposed to elevated Cu and were from D-Area parents. Our time-to-death analysis also suggests that either parental or larval metal contaminant exposure can result in deleterious effects, which are increased with the combination of the 2.…”
Section: Discussionsupporting
confidence: 89%
“…We exposed larval toads whose parents were sourced from either a metal-contaminated or a reference wetland to the presence or absence of Cu and/or predator cues from caged dragonflies in outdoor mesocosms; we then transferred metamorphs to terraria for 5 mo to measure performance, growth, and survival of juveniles. The results of the larval exposure on effects to metamorphosis are presented in a separate publication (Rumrill et al 2016), but, importantly, we found that both parental wetland source and larval exposure to Cu resulted in reduced size at metamorphosis. For our purposes in the present study, we expected to distinguish between carryover and latent effects seen post metamorphosis by assuming that carryover effects would be mediated through body size at metamorphosis and latent effects would occur via a direct relationship to a stressor experienced prior to metamorphosis.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…As copper levels in the environment reach some critical level, it triggers the detoxication system of the organism (Herkovits, Helguero, 1998). Elevated Cu levels can increase embryonic and larvae mortality (Lance et al, 2012(Lance et al, , 2013Xia et al, 2012;Flynn et al, 2015), also cause sublethal effects including embryonic deformities (Chen et al, 2007), impaired predator avoidance (Garcı´a-Munoz et al, 2009;Rumrill, et al, 2016) and other. The boundary at which copper transforms from an activator of biological processes into a toxicant is blurred not only because of the adaptation capacities of the organism, but also because of the process of development as such.…”
mentioning
confidence: 99%